The statue within: An autobiography - Jacob, François (USA Cold Spring Harbor Laboratory Press, 1995)
In a new preface to this special edition of his critically acclaimed memoir, Francois Jacob recalls the events that brought him to Cold Spring Harbor Laboratory in the early 1960's and taught him much about phage biology and the informal ways of American science. Throughout his book, Jacob demonstrates a scientist's eye for detail and a poet's instinct for the inner life, as he tells of a privileged Parisian boyhood, young love, heroism in war, and the fascination of life at the edge of scientific discovery.